Avances diagnósticos y terapéuticos en el manejo de la Osteoporosis. - Panchi Tacuri, Odalis Carolina (2024)
Osteoporosis is a disease characterized by an imbalance in bone remodeling, which leads to a decrease in bone density and deterioration of the bone's micro-architecture, generating susceptibility to fractures in the elderly and postmenopausal women. The objective of this research was to obtain updated information on diagnostic and therapeutic advances in the management of osteoporosis. For this, a basic non-experimental, descriptive, cross-sectional, and documentary research was developed, consisting of a literature review of documents published in the last five years related to the research topic. The universe comprised 90 documents, of which 43 formed the research sample. Health descriptors and Boolean operators were used. The main results highlight the description of the etiopathogenic mechanism of the disease; the main drugs and their pharmacological principle used in the disease were also described. Finally, the etiopathogenic mechanism was correlated with the pharmacological groups used in its treatment. In conclusion, several advances in osteoporosis management are presented, significantly improving clinical management and providing reliable bases for current and future medical practice.